5PSQ-041 Consumption of herbal medicine in patients on oral anticancer drugs: still a long way to go. (24th March 2020) - Huon, JF; Thierry, M; Lepelletier, A; Laurent, V; Saillard, J; Fronteau, C
Abstract : Background and importance: There are few data on the use of herbal medicines and the potential risks of herbal drug interactions (HDI) with oral anticancer drugs (OACD), even though their consumption is increasing. Aim and objectives: The aim of this study was to collect data on consumption of medicinal plants by patients on OACD and to assess the potential HDI and their knowledge among patients and physicians. Material and methods: This was an observational study conducted within a hospital outpatient pharmacy for 6 weeks. Patient interviews were carried out using a questionnaire on the following themes: phytotherapy products consumed, point of purchase, consumption objectives and awareness of health professionals. Potential HDI were evaluated using the MSKCC and Hedrine databases. A targeted questionnaire was sent to haematologists and physicians to assess their knowledge and needs. Results: Among the 59 included patients receiving OACD, 17% (n=10) were using phytotherapy. Of these 10 patients, 4 were taking herbal medicine as a complement to their anticancer treatment and the other 6 for another purpose (well being, cough, cold). The majority (70%) consumed on a regular basis on average of 2.4 different products. Four (40%) had informed a professional of their consumption. The products were mainly purchased in organic product shops (40%) and in pharmacies (20%), on the advice of a member of the family and friends (50%) or a health professional (40%). Five interactions were found. These were HDI at risk of hyperkalaemia, increased risk of bleeding and toxicity of OACD by reduced metabolism. Among the 21 physicians who answered the survey, a difference in practice between general practitioners and haematologists was highlighted. All doctors were seeking training in complementary medicine. Conclusion and relevance: The consumption of herbal medicines in patients treated with OACD is not negligible. Patients appear to be poorly or not informed about HDI, as well as doctors. The pharmacist has a major role to play in this context. Distribution of a recommendation guide could reduce the risk of HDI. References and/or acknowledgements: 1. Boiteux-Jurain M, Gérard B, Perrin-Bonnot, et al. Interactions between phytotherapy and oral anticancer drugs: development of a tool to assist in pharmaceutical analysis. Hosp Pharm Clin 2017;52(1). No conflict of interest.